2020
DOI: 10.21203/rs.3.rs-35102/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ninjurin 2 rs118050317 gene polymorphism and endometrial cancer risk

Abstract: Background: Endometrial cancer is one of the most common female reproductive system tumors. As a vascular susceptibility gene, Ninjurin2 (NINJ2) may involve in endometrial carcinogenesis. We conducted an association analysis between NINJ2 gene polymorphism and endometrial cancer risk.Methods: Five SNPs rs118050317, rs75750647, rs7307242, rs10849390 and rs11610368 of NINJ2 gene were genotyped in 351 endometrial cancer patients and 344 healthy controls. The clinical index difference between cases and controls we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…positively affects the progression of CRC and EMT formation through the regulation of miR-129-5p and DNMT3A [31]. Meanwhile, circPTPN22 inhibits the proliferation and metastasis of gastric cancer cells by inhibiting the EMT pathway through competitive miRNA binding [32]. To evaluate whether circ-SIRT1 knockdown affects EMT, thereby inhibiting cell migration and invasion, we measured the expression of EMT marker proteins in CRC cells depleted of circ-SIRT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…positively affects the progression of CRC and EMT formation through the regulation of miR-129-5p and DNMT3A [31]. Meanwhile, circPTPN22 inhibits the proliferation and metastasis of gastric cancer cells by inhibiting the EMT pathway through competitive miRNA binding [32]. To evaluate whether circ-SIRT1 knockdown affects EMT, thereby inhibiting cell migration and invasion, we measured the expression of EMT marker proteins in CRC cells depleted of circ-SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the expression of the EMT marker proteins N-cadherin and vimentin was decreased, while that of E-cadherin was increased, indicating that the loss of circ-SIRT1 expression can result in EMT inhibition. Several studies have reported on the interaction between circRNAs and proteins in tumors [32,33]. Here, we used the CircInteractome web tool to predict the proteins that could bind to circ-SIRT1 and selected the highest-ranked one, EIF4A3, for further investigation.…”
Section: Discussionmentioning
confidence: 99%